Effectiveness of Pharmacist-Led Brief Educational Intervention for Adherence to the Antibiotics for Lower Respiratory Tract Infections (EATSA) in Post-Conflict Rural Areas of Pakistan: Study Protocol for a Randomized Controlled Trial - Faiz Ullah Khan; Yu Fang (MDPI AG, 2021)
Globally, lower respiratory infections (LRTIs) are one of the most common infectious diseases whichaffect majority of the population and as a result of inappropriate antibiotics practices lead to antibiotic resistance (AR). An individual randomized control trial will be conducted in the post-conflict areas of Swat, Pakistan, through a random sampling method. Patients aged > 18 years will be recruited from five community pharmacies and assigned to equally sized groups to receive either pharmacist-led education interventions or usual care with no intervention. A total of 400 (control = 200, study = 200) patients will be included, with prescriptions comprised of antibiotics for LRTIs. The outcomes measured in both groups will be a combination of treatment cure rate and adherence, which will be assessed using the Morisky Medication Adherence Scale and pill count. The trial comprises pharmacist-led educational interventions to improve treatment outcomes for patients with LRTIs. This study might establish the groundwork for pharmaceutical care of LRTIs patients with antibacterial therapy and the future delivery of a care strategy for the improvement of LRTIs treatment outcomes in post-conflict, remote areas of the third world and LMICs.